Effective adoptive immunotherapy of triple-negative breast cancer by folate receptor-alpha redirected CAR T cells is influenced by surface antigen expression level. Issue 1 (December 2016) - Song, De-Gang; Ye, Qunrui; Poussin, Mathilde; Chacon, Jessica; Figini, Mariangela; Powell, Daniel
Abstract Background The poor prognosis and the limited efficacy of targeted therapy in patients with triple-negative breast cancer (TNBC) have raised the need for alternative therapies. Recent studies have demonstrated that folate receptor-alpha (FRα) may represent an ideal tumor-associated marker for immunotherapy for TNBC. Methods The aim of the present study was to apply a chimeric antigen receptor (CAR) approach for the targeting of FRα expressed on TNBC cells and evaluate the antitumor activity of CAR-engineered T cells in vitro and in vivo. Results We found that human T cells expressing a FRα-specific CAR were potent and specific killers of TNBC cells that express moderate levels of FRα in vitro and significantly inhibited tumor outgrowth following infusion into immunodeficient mice bearing an MDA-MB-231 tumor xenograft. However, the antitumor activity of the FRα CAR T cells was modest when compared to the same CAR T cells applied in an ovarian tumor xenograft model where FRα expression is more abundant. Notably, FRα CAR T cells induced superior tumor regression in vivo against MDA-MB-231 that was engineered for overexpression of FRα. Conclusions Taken together, our results show that FRα CAR T cells can mediate antitumor activity against established TNBC tumor, particularly when FRα is expressed at higher levels. These results have significant implications for the pre-selection of patients with high antigen expression levels when utilizing CAR-based adoptive T cell therapies of cancer in future clinical trials.